2013
DOI: 10.1158/0008-5472.can-12-1857
|View full text |Cite
|
Sign up to set email alerts
|

FGF-2 Disrupts Mitotic Stability in Prostate Cancer through the Intracellular Trafficking Protein CEP57

Abstract: Malignant tumors with deregulated FGF-2 expression such as prostate cancer are also frequently aneuploid. Aneuploidy can be caused by cell division errors due to extra centrosomes and mitotic spindle poles. However, a link between FGF-2 overexpression and chromosome missegregation has so far been elusive. Here, we show that FGF-2 rapidly uncouples centrosome duplication from the cell division cycle in prostate cancer cells through CEP57, an intracellular FGF-2-binding and trafficking factor. CEP57 was initiall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…These 4, all tumor promoters (22, 3133), were predicted to be significantly inhibited in old mice. Both FGF2 (31) and ANGPT2 (32) are angiogenesis-associated factors, whereas IL5 is involved in angiogenesis and immune response (34, 35) and TGFβ1 in many functions including vascular development and angiogenesis (36). FGF2 has also been shown to induce proliferation of fibroblasts through TGFβ1 signaling, which affects extracellular matrix (ECM) production (37).…”
Section: Resultsmentioning
confidence: 99%
“…These 4, all tumor promoters (22, 3133), were predicted to be significantly inhibited in old mice. Both FGF2 (31) and ANGPT2 (32) are angiogenesis-associated factors, whereas IL5 is involved in angiogenesis and immune response (34, 35) and TGFβ1 in many functions including vascular development and angiogenesis (36). FGF2 has also been shown to induce proliferation of fibroblasts through TGFβ1 signaling, which affects extracellular matrix (ECM) production (37).…”
Section: Resultsmentioning
confidence: 99%
“…The centrosomal protein CEP57 has been found to promote daughter centriole stability by modulating tubulin acetylation [33]. The Chlamydomonas homolog of Cep70, CRC70, promotes centriole assembly by recruiting spindle assembly abnormal protein 6 (SAS‐6) and Bld10p [16].…”
Section: Discussionmentioning
confidence: 99%
“…Cep57 has also been reported to be required for spindle pole integrity (16). In addition, a recent study reported that Cep57 is related to prostate cancer and is required for centriole duplication (32). Therefore, Cep57 regulates the cell cycle at multiple stages to ensure correct segregation of the genetic material during mitosis.…”
Section: Discussionmentioning
confidence: 99%